2008
DOI: 10.1039/b806097e
|View full text |Cite
|
Sign up to set email alerts
|

DFT/TD-DFT molecular design of porphyrin analogues for use in dye-sensitized solar cells

Abstract: Density functional theory (DFT) and time-dependent DFT calculations have been employed to model Zn meso-tetraphenylporphyrin (ZnTPP) complexes having different b-substituents, in order to design an efficient sensitizer for dye-sensitized solar cells. To calculate the excited states of the porphyrin analogues, at least the TD-B3LYP/6-31G* level of theory is needed to replicate the experimental absorption spectra. Solvation results were found to be invariant with respect to the type of model used (PCM vs. C-PCM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(87 citation statements)
references
References 56 publications
(84 reference statements)
2
83
0
1
Order By: Relevance
“…[12][13][14]22 TD-DFT (B3LYP/6-31G(d)) calculations of zinc porphine (ZnP), have shown that the FMOs are well separated from other MOs and are the major contribution to the Q and B bands, in agreement with the four-orbital model. 23 In addition to this, the B band also contains a minor contribution from lower lying orbitals.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…[12][13][14]22 TD-DFT (B3LYP/6-31G(d)) calculations of zinc porphine (ZnP), have shown that the FMOs are well separated from other MOs and are the major contribution to the Q and B bands, in agreement with the four-orbital model. 23 In addition to this, the B band also contains a minor contribution from lower lying orbitals.…”
mentioning
confidence: 65%
“…3 However, the cost and limited availability of ruthenium, coupled with its undesirable environmental impact has led to investigation of organic based materials for DSSC applications [4][5][6][7][8][9][10] Porphyrins have a number of desirable properties for use in a DSSC and have attracted a great deal of attention. 4,[9][10][11][12][13][14][15] They are able to harvest light over a wide spectral range which is crucial for good DSSC performance. 9 The long-lived excited states 9,16 of porphyrins and efficient electron transfer into the conduction band of TiO 2 17 are also properties which make them effective DSSC dyes.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular orbitals were visualized by GaussView 3.0 software. [33] The method has been widely used for geometry optimizations and electronic calculations of porphyrin derivatives due to its accuracy, [4,5,6,34,35] which was further validated by the very similar bond angles and lengths in the optimized structures of MTPP-AOP (M = 2H + , Zn 2+ , Cu 2+ ) and single-crystal structures.…”
Section: Photocurrent-voltage Measurementsmentioning
confidence: 99%
“…As a model for nanocrystallinity the HOMO and LUMO energies of bare cluster (TiO 2 ) 38 are -7.23 and -4.1 eV, respectively, resulting in a E gap of 3.13 eV [26]. Generally energy gap more than 0.2 eV between the LUMO of the dye and the conduction band of the TiO 2 is necessary for effective electron injection [27].…”
Section: Geometriesmentioning
confidence: 99%